EFFECTS OF INTEREST RATE STRUCTURE AND ENERGY PRICES ON MANUFACTURING OUTPUT IN NIGERIA - OYAROMADE, Rasheed; ISAYOMI, Abiodun Samuel; IBRAHIM-AYEDE, Sulaiman (Journal of Social Sciences)
Until recent years, the performance of the Nigeria’s manufacturing sector has been characterized by downward pressures. Given the present shocks in the global energy markets and upward review of borrowing costs by the Central Bank of Nigeria, the historical developments around the manufacturing output appear to be subject to renewal. Consequently, this study investigates the impact of interest rate structure and energy pricing on the Nigerian manufacturing output from 1980 to 2021. Secondary data obtained from World Development Indicators and the CBN’s Statistical Bulletins were anchored by an autoregressive distributed lag (ARDL) model and error correction modelling. The findings revealed that manufacturing output is inelastic in its response to changes in interest rate while it is elastic in its response to energy price. This is less puzzling as the Nigerian manufacturers seem to favour availability of credit facilities over low interest rates. Also, productive activities respond immediately to a given shock in the energy price, especially the price of diesel. On this basis, this paper concludes that energy pricing is a strong predictor of Nigeria’s manufacturing output. Consequently, policy makers should institute a preferential treatment on energy distribution towards the manufacturers. This would make production more attractive, thereby boosting their capacity utilization.